Islamic Law Analysis of the Use of Paylater with Additional Fees from the Perspective of the Sustainable Development Goals (SDGs) - Wardana, Arwanda Kusuma; Muthoifin, M (Universitas Muhammadiyah Surakarta, 2025)
This study examines the use of PayLater services, which impose additional costs such as handling fees (1%) and late fines (5%), in relation to Islamic jurisprudence, particularly the prohibitions of riba and gharar. The analysis is framed within fiqh muamalah, addressing the concepts of riba nasi'ah (interest from delayed payment), gharar (contractual uncertainty), and the legitimacy of contracts such as qardh (interest-free loans), murabahah (profit-margin sales), and ijarah (leasing). Employing a doctrinal qualitative approach, this research analyzes authoritative sources (Qur'an, hadith, classical fiqh, fatwas) alongside the framework of maqasid al-shariah to assess socioeconomic implications.The findings demonstrate that the fee structure of PayLater services contradicts sharia principles: it qualifies as riba nasi'ah and entails gharar due to lack of transparency, rendering the contracts fasid (invalid) for violating clarity of price (tsaman) and transaction object. Although PayLater services promote financial inclusion (hifz al-mal), they simultaneously encourage excessive consumption, threatening hifz al-aql (intellect), hifz al-din (faith), and leading to israf (wastefulness).The study highlights the need for structural reforms, including replacing interest with transparent fixed administrative costs, standardizing digital contracts, enhancing Islamic financial literacy, and regulatory intervention by the OJK through halal certification and supervision. Its novelty lies in offering a transformative framework for Sharia-compliant PayLater models, such as mudharabah (profit-sharing) or ijarah muntahiya bi al-tamlik (lease-to-own), while integrating a comprehensive maqasid-based evaluation of consumer behavior. This contribution not only provides practical recommendations for aligning fintech innovation with Islamic law but also addresses the broader goals of sustainable and equitable development.